Exploring and Mobilizing the Gene Bank Biodiversity for Wheat Improvement. - Deepmala Sehgal; Prashant Vikram; Carolina Paola Sansaloni; Cynthia Ortiz; Carolina Saint Pierre; Thomas Payne; Marc Ellis; Ahmed Amri; César Daniel Petroli; Peter Wenzl; Sukhwinder Singh (PLoS ONE, 2015)
Identifying and mobilizing useful genetic variation from germplasm banks to breeding programs is an important strategy for sustaining crop genetic improvement. The molecular diversity of 1,423 spring bread wheat accessions representing major global production environments was investigated using high quality genotyping-by-sequencing (GBS) loci, and gene-based markers for various adaptive and quality traits. Mean diversity index (DI) estimates revealed synthetic hexaploids to be genetically more diverse (DI= 0.284) than elites (DI = 0.267) and landraces (DI = 0.245). GBS markers discovered thousands of new SNP variations in the landraces which were well known to be adapted to drought (1273 novel GBS SNPs) and heat (4473 novel GBS SNPs) stress environments. This may open new avenues for pre-breeding by enriching the elite germplasm with novel alleles for drought and heat tolerance. Furthermore, new allelic variation for vernalization and glutenin genes was also identified from 47 landraces originating from Iraq, Iran, India, Afghanistan, Pakistan, Uzbekistan and Turkmenistan. The information generated in the study has been utilized to select 200 diverse gene bank accessions to harness their potential in pre-breeding and for allele mining of candidate genes for drought and heat stress tolerance, thus channeling novel variation into breeding pipelines. This research is part of CIMMYT's ongoing 'Seeds of Discovery' project visioning towards the development of high yielding wheat varieties that address future challenges from climate change.